Analisis Pengaruh Harga, Inovasi Rasa, dan Daya Tarik Kemasan Minuman Teh Jumbo terhadap Preferensi Konsumen Teh Botol Pabrikan : Studi Kuantitatif tentang Perilaku Konsumen di Jawa, Indonesia. - Budiarto, Gatot; Suprihati; Samanto, Hadi (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2025)
The packaged tea beverage industry in Indonesia, once a dominant player, is currently facing a decline in market performance. This trend is accompanied by the rapid rise of “Teh Jumbo”—a large-sized, street-sold iced tea that is affordable and highly favored by consumers across Java. This study was prompted by the concern that the growing popularity of Teh Jumbo might be influencing the declining preference for factory-produced bottled tea. The research aims to investigate the impact of price, flavor innovation, and packaging appeal of Teh Jumbo on consumer preferences for branded bottled tea. A quantitative approach was employed using a questionnaire distributed to respondents in several regions across Java, and data were analyzed using multiple linear regression. The findings reveal that all three factors significantly influence consumer preferences, with flavor innovation emerging as the most dominant. These insights provide a better understanding of shifting consumer behavior in the competitive tea beverage market. Keywords : Consumer Preference, Price, Flavor Innovation, Packaging Appeal, Teh Jumbo